Community Engagement in an Urban Elementary School: A Critical Ethnographic Inquiry - Shannon, Katheryn (My University, 2014)
The challenges of engaging families in poverty have been documented and strategies for addressing the unique needs of communities of poverty have been put forward (Hands & Hubbard, 2011; Hiatt-Michael & Hands, 2010; Raffo et al., 2010; Rehman, 2011). The purpose of this study is to examine participation to reveal the nature of community engagement and identify who participates in these activities. This critical ethnographic inquiry engages an ethic of care and a place-based theoretical lens to explore authentic participation within a single urban school; the elementary school employs the equity strategy of community schooling to support conditions for learning (Cummings, Dyson, & Todd, 2011; Gruenewald, 2003; Noddings, 1989, 1992). An archive of school and community data consisting of experiences, enquiries, and document examination support three ends-in-view for community engagement: community service, student enrichment, and community development (Wolcott, 2008; Anderson, 1998). Exploration of these ends-in-view reveals who participates and to what end members of the community are involved in decision-making and action to address relevant social issues in this central city context. Findings indicate hegemonic practices which perpetuate poverty circumstance are inherent within the community engagement activities experienced and described (Fine, 1994; Raffo et al., 2010). Closer examination of participation in decision-making and action within the community reveal few opportunities for community members to be embedded in or lead decision-making processes to address relevant social issues of place. Finally, authentic participation is re-framed from a place-based perspective of care and warrants employment of socially just practices which grow leadership from within the community as advocates for the community and to address marginalization and exploitation within this urban place (Baptist & Theoharis, 2011).
Keywords: Education, Administration.